The Effect of Profitability and Capital Structure on the Share Price of IDX Non-Cyclical Sector Companies on the Indonesia Stock Exchange - Khodijah Abdurahman; Jubaedah Jubaedah (Budapest International Research and Critics University, 2022)
This study is a quantitative study that aims to determine the effect of profitability and capital structure on the stock price of companies in the IDX NON CYCLICAL index. This study uses 56 companies listed in the IDX NONCYCLICAL index as samples and the 2016-2020 period of observation. The sample selection was carried out using proportionate stratified random sampling. Profitability variable is measured by Return to Equity Ratio and Capital Structure is measured by Debt-to-Equity Ratio. The company's stock price data is taken 7 days after the publication date of the company's annual financial statements. Hypothesis testing is done by using Multiple Linear Regression Analysis with e-views program, with a significance level of 5%. The results of the test show that (1) profitability has a positive effect on the company's stock price and (2) capital structure has a positive effect on the company's stock price.